Context and Implications Document for: Is informal education the answer to increasing and widening participation in STEM education?. Issue 2 (28th February 2017) - Banerjee, Pallavi Amitava
Abstract : This guide accompanies the following article: Banerjee, P. A (2017) Is informal education the answer to increasing and widening participation in STEM education?. Review of Education, DOI:10.1002/rev3.3093